2015
DOI: 10.1095/biolreprod.115.130856
|View full text |Cite
|
Sign up to set email alerts
|

The Family Secrets of Avian Egg-Specific Ovalbumin and Its Related Proteins Y and X

Abstract: The ovalbumin gene family in Gallus gallus is composed of three homologous genes located within a 46 kb locus on chromosome 2: ovalbumin, ovalbumin-related protein Y (OVAY), and ovalbumin-related protein X (OVAX) genes. The expression of these genes in hen oviduct is under estrogen control, but their relative hormonal responsiveness and subsequent protein concentration in egg, is distinctive. Interestingly, all three proteins lack the classical signal peptide for secretion. Ovalbumin, OVAX, and OVAY belong to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Furthermore, the protein content and composition within different muscles of the same animal will also vary (e.g., light meat compared to dark meat in a chicken), as will the different proteins within any particular muscle (e.g., myofibrillar proteins are considered high quality complete proteins, while the stromal proteins in muscle are considered a low quality incomplete proteins [41] (Table 1). Eggs also contain structural proteins, along with hundreds of other functional proteins that have evolved to assist with various physiological processes revolving around embryonic nourishment and development [42]. The specific protein fractions are very different between the egg yolk and white [20] (Table 1).…”
Section: Protein Classifications and Quality Scores Are Of Limitedmentioning
confidence: 99%
“…Furthermore, the protein content and composition within different muscles of the same animal will also vary (e.g., light meat compared to dark meat in a chicken), as will the different proteins within any particular muscle (e.g., myofibrillar proteins are considered high quality complete proteins, while the stromal proteins in muscle are considered a low quality incomplete proteins [41] (Table 1). Eggs also contain structural proteins, along with hundreds of other functional proteins that have evolved to assist with various physiological processes revolving around embryonic nourishment and development [42]. The specific protein fractions are very different between the egg yolk and white [20] (Table 1).…”
Section: Protein Classifications and Quality Scores Are Of Limitedmentioning
confidence: 99%
“…Whatever the pattern each nsSNP takes in the interruption of the ovalbumin family, the current finding indicated that these nsSNPs seriously affect the structure, function, and stability of ovalbumin family, which have a series of deleterious consequences on the biological pathways in which these proteins involved, such as egg defense activity, embryonic fertilization and development (Liu et al 2015;Akazawa et al 2019). Accordingly, its noteworthy to distinguish that both H365P and I167T, being the most deleterious nsSNPs in OVALX and OVALY, respectively, should take priority in terms of reducing antimicrobial activity in case of OVALX (Guyot et al 2016), or damaging embryonic development in case of OVALY (Da Silva et al 2015). This observation is particularly interesting, knowing that once these amino acid substitutions detected in a particular breed, serious precautions should be taken for breeders with respect to the handling of this breed.…”
Section: Discussionmentioning
confidence: 99%
“…All these three genes are mainly expressed in the oviduct (Sugimoto et al 2001), and more specifically by tubular gland cells of the chicken's magnum (Rehault-Godbert et al 2013). Sequences alignment of these three genes have shown a sequence identity of 73 % between OVAL and OVALX, of 72 % between OVAL and OVALY, and 82 % between OVALX and OVALY genes (Da Silva et al 2015). Although OVAL, OVALY, and OVALX proteins have exerted high homology in their primary sequences, distinct and subtle physicochemical and structural differences have exhibited among them that might be associated with specific function on each one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 300 proteins have been identified in the EW, 8 of which account for approximately 90% of the protein content: OVAL (54%), TF (12%), ovomucoid (SPINK7, 11%), ovoglobulin G 2 (BPIFB2/G2/TENP, 4%), ovomucin (3.5%), LYZ (3.4%), ovoinhibitor (SPINK5, 1.5%), and ovoglycoprotein (ORM1, 1%) [55, 57-62]. OVAL likely serves as a nutritional source of amino acids for the embryo [63]. OvoDA1/gallin, AvBD11, TF, LYZ, ovomucin, SPINK5, and SPINK7 participate in the antimicrobial activity of EW [64-67].…”
Section: Egg Basic Structures and Innate Immunitymentioning
confidence: 99%